The substance abuse problems - Sidney Cohen (The Harworth Press, 1981)
This book describes the abuse of many legal and illigal drugs and details the effects of that abuse. It analyzes the trends in drug abuse and relates the global nature of the problem. It also describes the various diagnoses and treatments of certain abuse problems. And it concludes with a discussion of special situations and special groups involved in the abuse of drugs.